(untitled) (INTEGRATION PROCEEDING, 2023)
Ammonia contamination in river water can harm the water biota of the Barito River which is now polluted with ammonia compounds of 4.425 mg/L. People often consume fish caught from the Barito River which is suspected to be polluted with ammonia compounds, one of which is Lawang fish. Based on Permenkes No. 492 of 2010, the level of ammonia that can enter the human body is 1.5 mg/L. Ammonia levels can be reduced by immersing it in citric acid, which is a weak organic acid found in the leaves and fruits of citrus plants, one of which is Limau Kuit. Limau Kuit is a type of citrus typical of South Kalimantan and contains citric acid which is thought to reduce ammonia levels. This study is to knowing the potential of Limau Kuit filtrate in reducing ammonia levels in Lawang fish and the effect of different concentrations of Limau Kuit fruit filtrate on reducing ammonia levels in Lawang fish. In this study, the type of research was Experimental Design, then the research design was carried out by Post Test only control group design to see the decrease in the ammonia content in Lawang fish with UV-Vis Spectrophotometry instruments and data analysis using One Way Anova with purposive sampling technique. The results showed that there was a decrease in ammonia levels in fish samples that were soaked by the Limau Kuit filtrate and obtained the percentage of decrease in each variation in the concentration of the Limau Kuit filtrate, namely in fish 1 with filtrate soaking 25% (9.1%), 50% (25.7%), 75% (32.4%) and 100% (21.6%) then fish 2 with filtrate soaking 25% (6.1%), 50% (8.5%), 75% (18.4) and 100% (16.6%) and fish 3 with filtrate soaking 25% (2.8%), 50% (6.8%), 75% (20%) and 100% (31.7%). The results showed that the Limau Kuit filtrate can reduce ammonia levels in fish by immersion of opimal using the Limau Kuit filtrate of 75%.